Early-Onset Diabetes Mellitus in Chromosome 8p11.2 Deletion Syndrome Combined With Becker Muscular Dystrophy - A Case Report - Cao, Conghui; Wang, Xiaoli; Zhao, Xiaojuan (Frontiers in Endocrinology, 2022)
Background: Chromosome 8p11.2 includes several key genes in development such as the FGFR1, ANK1, KAT6A, and SLC20A2 genes. Deletion of this fragment causes a contiguous gene syndrome. Currently, few cases of interstitial deletion of whole 8p11.2 have been reported. We report a rare case of 8p11.2 deletion syndrome with the unique phenotypes, presenting with early-onset diabetes. Case description: A 20-year-old man with a 1-year history of diabetes mellitus was admitted to the Endocrinology Clinic. Physical examination revealed the dysmorphic facial features, and broad and foreshortened halluces. Laboratory examination indicated spherocytosis anemia, and hypogonadotropic hypogonadism. Bone mineral density analysis showed decreased bone density in the lumbar vertebrae. Brain CT showed calcification. Whole-exome sequencing revealed a 7.05-Mb deletion in 8p11 containing 43 OMIM genes, and a large in-frame deletion of exons 48–55 in the DMD gene. Metformin was given to the patient after which his blood glucose was well controlled. HCG was injected subcutaneously and was supplemented with calcium and vitamin D, which led to an improvement in the patient’s quality of life. Conclusion: We report a rare case of 8p11.2 deletion syndrome with unique phenotypes, and early-onset diabetes. It is challenging for endocrinologists to simultaneously reconcile a combination of these diseases across multiple disciplines. We discussed the influencing factors of early-onset diabetes in this patient and speculated that it was caused by complex interactions of known and unknown genetic backgrounds and environmental factors.